Loneliness epidemic dan krisis kesehatan mental global: Tinjauan teori humanistik Carl Rogers - Astuti, Elly Novie (Maliki Interdisciplinary Journal, 2025)
Millions of people worldwide are impacted by the loneliness epidemic, which has grown into a serious global mental health catastrophe. Loneliness and mental health illnesses are becoming far more common, according to recent studies, particularly among teenagers and young people. In this study of the literature, Carl Rogers’ humanistic theory more especially, the person-centered therapeutic approach is used to examine the loneliness epidemic issue. This study examines how the loneliness crisis can be interpreted as an expression of the discrepancy between the ideal and actual self-concepts, as well as how the social environment can either promote or impede healthy mental development, by incorporating Rogers’ ideas of congruence, self-actualization, and unconditional positive regard. The results show that humanistic methods and client-centered therapy provide insightful viewpoints for dealing with the worldwide mental health epidemic. As long-term solutions to the loneliness epidemic, this study highlights the significance of implementing Rogers’ ideas in a contemporary setting, such as fostering self-actualization, creating environments that offer unconditional positive regard, and building inclusive social support.